Harnessing the determinants of peer-to-peer (p2p) lending success in Malaysia - Nur Asyiqin Ramdhan; Imbarine Bujang; Amirul Afif Muhamat; Jaratin Lily (Springer Science and Business Media Deutschland GmbH, 2025)
FinTech lending through peer-to-peer (P2P) platforms transpired from the funding innovation categorized as alternative financing. Although financing access through P2P lending is convenient, the industry’s long-term viability is dubious due to the collapse of platforms. The information technology advancement utilized in the platform suffers a credit risk through information asymmetry. This paper investigates the short- and long-term dynamics between the platform information and macroeconomic variables in determining P2P funding success in Malaysia. Using ARDL, the relationship between platform interest rates, loan tenure, investment size, BLR, and inflation toward P2P successful fundraising was studied. Findings show investment size, BLR, and inflation statistically significant with both short- and long-term P2P funding success. While loan duration was revealed to have a significant effect on the short-term P2P funding success only. We also discovered a contra result for the platform interest rate, where an insignificant relationship was indicated.